Experimental intraocular infection of exotic cockerels with field strain of velogenic Newcastle disease virus in Nigeria - Badau, Samaila Jonathan; Hassan, Shehu Usman; El-Yuguda, Abdul-Dahiru; Igbokwe, Ikechukwu Onyebuchi (Journal of Advanced Veterinary and Animal Research, 2015)
Experimental intraocular (conjunctival) infection of exotic cockerels with a new field strain of viscerotropic velogenic Newcastle Disease Virus (NDV) was conducted to explore the concurrence of some pathological changes with humoral immune responses. After the NDV infection of 4-week-old cockerels, pathologic changes and antibody responses were observed. The clinical signs observed after the artificial inoculation included inappetence, depression, diarrhea, dyspnea, wing and leg paralysis, torticollis and weight loss. Morbidity due to the NDV was 100%, but mortality was 80% by day 18-21 post-infection. Early hyperthermia followed by terminal hypothermia, decreased packed cell volume (PCV), and 231.4 folds peak-antibody response were observed. Necrotic and/or inflammatory lesions were present in the proventriculus, intestine, liver, spleen, kidney and brain. Neurologic and digestive tract perturbations occurred in 10% and 85% of cases, respectively. The disease consistently caused stunted growth, decreased PCV, and necro-inflammatroy lesions concurrent with antibody response, suggesting probable involvement of immune- mediated mechanisms and cell membrane desialylation by viral neuraminidase in the pathogenesis. http://dx.doi.org/10.5455/javar.2015.b111